Eco-friendly antisolvent enabled inverted MAPbI3 perovskite solar cells with fill factors over 84%. Issue 10 (28th April 2021) - Cui, Yuying; Wang, Shurong; Li, Chengbo; Wang, Aili; Ren, Jing; Yang, Chenguang; Chen, Bin; Wang, Zhen; Hao, Feng
Abstract : A green co-antisolvent of propyl acetate and diethyl ether is induced to adjust the degree of supersaturation during the perovskite deposition, enabling a power conversion efficiency of 20.61% with a fill factor of 84.49% for inverted solar cells. Abstract : Antisolvent assisted crystallization has been most widely applied in depositing high-quality perovskite thin films for efficient perovskite solar cells (PSCs). However, the toxicity of common antisolvents (chlorobenzene, toluene etc .) involved in perovskite processing raises serious environmental and health concerns for large-scale implementation. Herein, a green co-antisolvent of propyl acetate is induced to adjust the degree of supersaturation in diethyl ether, enabling pinhole-free, smooth, and uniform perovskite thin films. By carefully controlling the polarity of the antisolvents, the deposited perovskite film showed higher electron mobility and suppressed defect density than that of the control film. As a result, a high power conversion efficiency up to 20.61% was achieved in a p–i–n inverted MAPbI3 PSC with an impressive fill factor (FF) over 84%. The high FF is mainly attributed to the attenuated ideal factor and improved diode junction quality. This approach provides a greener path to the sustainability and scalability of the emerging PSC technology.